A collaborative review of the current concepts and challenges of anastomotic leaks in colorectal surgery. (January 2017) - Vallance, A.; Wexner, S.; Berho, M.; Cahill, R.; Coleman, M.; Haboubi, N.; Heald, R. J.; Kennedy, R. H.; Moran, B.; Mortensen, N.; Motson, R. W.; Novell, R.; et al.
Abstract: The reduction of the incidence, detection and treatment of anastomotic leakage (AL) continues to challenge the colorectal surgical community. AL is not consistently defined and reported in clinical studies, its occurrence is variably reported and its impact on longterm morbidity and health‐care resources has received relatively little attention. Controversy continues regarding the best strategies to reduce the risk. Diagnostic tests lack sensitivity and specificity, resulting in delayed diagnosis and increased morbidity. Intra‐operative fluorescence angiography has recently been introduced as a means of real‐time assessment of anastomotic perfusion and preliminary evidence suggests that it may reduce the rate of AL. In addition, concepts are emerging about the role of the rectal mucosal microbiome in AL and the possible role of new prophylactic therapies. In January 2016 a meeting of expert colorectal surgeons and pathologists was held in London, UK, to identify the ongoing controversies surrounding AL in colorectal surgery. The outcome of the meeting is presented in the form of research challenges that need to be addressed.